Potential use of recycled materials on rooftops to improve thermal comfort in sustainable building construction projects - Ahmad, Mushtaq; Ali, Miram; Turi, Jamshid Ali; Manan, Aneel; Al-Dala’ien, Rayeh Nasr Salam; Rashid, khalid (Frontiers in Built Environment, 2022)
The study has two objectives. First, it experimentally measures the indoor and outdoor temperatures of a building in Peshawar and conducts validation with CFD modeling. Second, it simulates the building with the addition of locally available, natural, and recycled insulator materials on the rooftop to keep the indoor environment within a comfortable temperature range, especially in the winter and summer seasons. To achieve these objectives, experimental temperature data for January and June were recorded and validated, followed by a simulation, using ANSYS-Fluent 16 CFD, of the residential building with the application of waste thermal insulators such as straw bale, sheep wool, and recycled glass materials on the rooftop to reduce the indoor temperature. Experimental temperature measurement showed that the lowest recorded indoor temperature was 15°C on 2 January 2022 and that the highest recorded indoor temperature was 41°C on 11 June. The predicted and validated temperature results were similar, with a slight difference of less than 15%. Recycled glass positively and significantly reduced the indoor temperature in summer by 10.2% and thermal amplitude by 48.3%, with a time lag increase of 100% and an increase in the period of comfort hours of 380%. In winter, the daily average temperature increased by 7.4%, thermal amplitude was reduced by 59.3%, and the time lag increased by 100% in comparison with the baseline case results. The study concludes that recycled glass distribution gives the best improvement compared to straw bale and sheep wool.